2013
DOI: 10.1162/jocn_a_00373
|View full text |Cite
|
Sign up to set email alerts
|

The Neurobiology of Rhyme Judgment by Deaf and Hearing Adults: An ERP Study

Abstract: We used electrophysiology to determine the time-course and distribution of neural activation during an English word rhyme task in hearing and congenitally deaf adults. Behavioral performance by hearing participants was at ceiling and their ERP data replicated two robust effects repeatedly observed in the literature. First, a sustained negativity, termed the contingent negative variation (CNV), was elicited following the first stimulus word. This negativity was asymmetric, being more negative over the left than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…More recently, MacSweeney, Goswami, and Neville (2013) contrasted ERP responses in deaf and hearing adults as they performed rhyme judgments to sequentially presented written words (e.g., chair/bear pairs in which the rhyme decision could only be made using phonological knowledge). Only data from deaf participants who performed above chance ( n = 9) were analyzed (hearing participants were at ceiling).…”
mentioning
confidence: 99%
“…More recently, MacSweeney, Goswami, and Neville (2013) contrasted ERP responses in deaf and hearing adults as they performed rhyme judgments to sequentially presented written words (e.g., chair/bear pairs in which the rhyme decision could only be made using phonological knowledge). Only data from deaf participants who performed above chance ( n = 9) were analyzed (hearing participants were at ceiling).…”
mentioning
confidence: 99%
“…The lack of behavioural differences between the groups further indicates that the tasks are comparable with each other. Previous work on deaf signers and hearing individuals has shown that there are similarities between the neural substrates of phonological processing across the modalities of sign and speech (Aparicio, Gounot, Demont, & Metz-Lutz, 2007;Macsweeney et al, 2013;MacSweeney et al, 2008), suggesting an amodal representation. In the present work, a different pattern was obtained.…”
Section: IImentioning
confidence: 94%
“…Evidence from both electrophysiological and brain imaging studies has shown similarities in the engagement of neural networks across the language modalities of speech and sign during phonological processing, suggesting that phonology may be represented amodally or supramodally (Macsweeney, Goswami, & Neville, 2013;MacSweeney, Waters, Brammer, Woll, & Goswami, 2008). However, there are modality-specific elements in phonological processing, evidenced by activation modulation relating to language-modality and hearing status (MacSweeney et al, 2008).…”
Section: IImentioning
confidence: 99%
“…Interestingly, a recent publication examined phonological processing using behavioral and ERP measures of text-based rhyme judgments in prelingually deafened adults who were native sign language users (MacSweeney et al, 2013). MacSweeney et al (2013) found similar N400 (referred to as N450) distribution, amplitude modulation and onset latencies in the deaf and the normally hearing participants, when only individuals who had performed above chance level behaviorally (n = 9) were included. This was in spite of a significantly lower performance when measured by rhyme judgment accuracy in the deaf participants.…”
Section: Rhyme Judgment and Explicit Processingmentioning
confidence: 99%
“…The present results show that the R-O+ condition may be important to include when examining rhyme judgments in individuals with HI. The study by MacSweeney et al (2013) described above did not use this condition but it would be interesting to investigate if an N2-like response would also be elicited in deaf participants.…”
Section: Rhyme Judgment and Explicit Processingmentioning
confidence: 99%